Effects of damping and helical fillets on galloping vibration of stay cable installed with a rectangular lamp. Issue 8 (June 2023) - An, Miao; Li, Shouying; Chen, Zhengqing
Lamps attached on the stay cable can change the stable circular cross-section of the stay cable, which is easy to cause galloping vibration. Stay cables of the Kuipu bridge in the Fuzhou City of China were equipped with damper and helical fillets. After the installation of rectangular lamps on this bridge, no obvious vibration of the stay cables was observed. This is totally different from another bridge, the Kuimen bridge in the Chongqing City of China, which has been recently reported by the authors. The purpose of this study is to clarify the effects of the helical fillets and the structural damping on galloping vibration. The features of galloping vibration of the stay cable attached to a rectangular lamp were carefully studied, and the effectiveness of damping and helical fillets in reducing the galloping vibration was evaluated. First, the force measurement wind tunnel tests on the segmental test model were carried out, and the lift and drag coefficients of the stay cable attached to the rectangular lamp were measured. The dangerous wind attack angle of galloping vibration was predicted by the galloping force coefficient. Second, 3-dimensional vibration measurement wind tunnel tests were carried out to measure the wind-induced response of the cable-lamp test models. The variation of wind-induced response of stay cable with yaw angle and wind velocity was measured for test models with and without helical fillets. In the test, the features of wind-induced vibration were studied at the damping level of 0.1%, 0.6%, 0.7%, 0.8%, and 1.0%. According to Den Hartog's theory, the minimum coefficient of galloping force is about −9.8. The experimental results of 3-dimensional vibration measurement wind tunnel tests show that the helical fillets wrapped on the cable surface can enhance the critical wind velocity to a certain extent, but the critical wind velocity is still far lower than the design wind velocity. When the damping ratio of the stay cable is up to 1.0% ( S C = 35.1), the galloping vibration of the stay cable attached to a rectangular lamp on the Kuipu Bridge can be effectively mitigated.